Vertical Linkages and Multinational Enterprises in Developing Countries - LIM, Linda Y. C. (Institutional Knowledge at Singapore Management University, 1982)
Many studies have concluded that multinational firms do not create significant technical and other vertical linkages in developing host countries. This case study of three multinational firms in the export-oriented electronics industry in Singapore shows that under certain conditions multinational firms can lead in creating local vertical linkages. It suggests that restrictive government policies to increase local purchases may not be necessary, effective or desirable in promoting local linkages by export-oriented multinational firms that respond primarily to international market conditions. The Singapore experience poinst to the importance of a healthy investment climate and rapid economic growth in encouraging multinational firms to forge local linkages.